SYNTACTIC COMPLEXITY IN THE READING MATERIALS OF ENGLISH FOR ACADEMIC PURPOSES LEVELS 1 â 3 - Wijanti, Widdy (LLT Journal: A Journal on Language and Language Teaching, 2017)
In Indonesia, English is still considered as a foreign language and has become a crucial subject of study especially in the university level. For this reason, English for Academic Purposes has been conducted in the first year of college level for many years. Unfortunately, although many Asian countries including Indonesia have run the EAP course, the output is that there are still many Indonesian students who do not meet the vocabulary size and syntactic complexity that are expected while their learning process in the university. This results lower grades that they have in their assignments. Therefore, the recent study is aimed at evaluating the reading materials of EAP, especially in measuring the syntactic complexity containing in the texts as it is strongly believed in English learning that a good language output comes from a good language input. The data is taken from the collections of reading materials taken from EAP course Level 1, Level 2, and Level 3 which are compulsory subjects for students at Sampoerna University in their first 2 years of study. The data then is processed using the Syntactic Complexity Analyzer (Ai & Lu, 2013). The findings showed that the reading materials of EAP course Level 3 text is mainly suggested to be reviewed and revised in order to fulfill the five categories of syntactic complexity, i.e. the length of production unit, the sentence complexity, the subordination, the coordination, and the particular structure.Â DOI: doi.org/10.24071/llt.2017.200204